Surface Rupture and Distributed Deformation Revealed by Optical Satellite Imagery: The Intraplate 2016 Mw 6.0 Petermann Ranges Earthquake, Australia. Issue 17 (7th September 2019) - Gold, Ryan D.; Clark, Dan; Barnhart, William D.; King, Tamarah; Quigley, Mark; Briggs, Richard W.
Abstract: High‐resolution optical satellite imagery is used to quantify vertical surface deformation associated with the intraplate 20 May 2016 Mw 6.0 Petermann Ranges earthquake, Northern Territory, Australia. The 21 ± 1‐km‐long NW trending rupture resulted from reverse motion on a northeast dipping fault. Vertical surface offsets of up to 0.7 ± 0.1m distributed across a 0.5‐to‐1‐km‐wide deformation zone are measured using the Iterative Closest Point algorithm to compare preearthquake and postearthquake digital elevation models derived from WorldView imagery. The results are validated by comparison with field‐based observations and interferometric synthetic aperture radar. The pattern of surface uplift is consistent with distributed shear above the propagating tip of a reverse fault, leading to both an emergent fault and folding proximal to the rupture. This study demonstrates the potential for quantifying modest (<1 m) vertical deformation on a reverse fault using optical satellite imagery. Key Points: The 20 May 2016 Mw 6.0 Petermann Ranges earthquake, Australia resulted from reverse faulting Iterative Closest Point (ICP) comparison of preearthquake and postearthquake DEMs derived from optical satellite imagery A 21‐km‐long rupture with maximum vertical deformation of 0.7 m and broad 0.5‐ to 1‐km‐wide deformation zone